2013
DOI: 10.1007/s00246-013-0772-7
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Stroke Volume Variation Measured by a Noninvasive Cardiac Output Monitor to Predict Fluid Responsiveness in Mechanically Ventilated Children

Abstract: Continuous noninvasive cardiac output monitoring (NICOM) is a clinically useful tool in the pediatric setting. This study compared the ability of stroke volume variation (SVV) measured by NICOM with that of respiratory variations in the velocity of aortic blood flow (△Vpeak) and central venous pressure (CVP) to predict of fluid responsiveness in mechanically ventilated children after ventricular septal defect repair. The study investigated 26 mechanically ventilated children after the completion of surgery. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 21 publications
2
59
1
Order By: Relevance
“…One study on mechanically ventilated pediatric patients showed that respiratory changes in peak velocity outperformed SVV in identifying those who were volume responsive, with an AUC of 0.95. 72 These findings were confirmed in two other studies on a similar patient population. 73,74 …”
Section: Respiratory Variation Of Echocardiographic Parameterssupporting
confidence: 70%
“…One study on mechanically ventilated pediatric patients showed that respiratory changes in peak velocity outperformed SVV in identifying those who were volume responsive, with an AUC of 0.95. 72 These findings were confirmed in two other studies on a similar patient population. 73,74 …”
Section: Respiratory Variation Of Echocardiographic Parameterssupporting
confidence: 70%
“…Four studies used colloids as fluid bolus, one study used crystalloid, and one study did not report type of fluid given. Four studies were performed in the operating room during congenital heart surgery or craniosynostosis repair [14, 2123], and two studies were performed in the PICU [13, 20]. SVV was tested by non-invasive measures such as NICOM (non-invasive cardiac output monitor) and USCOM (ultrasonic cardiac output monitor) in four studies, whereas two studies used invasive measures including PiCCO (pulse index continuous cardiac output) and Mostcare.…”
Section: Resultsmentioning
confidence: 99%
“…This could explain the differences in threshold values observed across studies. In most of these studies, the median or mean age of the population was less than 3 years, but the ranges did vary . Consequently, we cannot exclude age as a confounding factor, particularly with respect to the cutoff value of ΔVPeak in infants and newborns.…”
Section: Discussionmentioning
confidence: 99%